2014
DOI: 10.1371/journal.pone.0088201
|View full text |Cite
|
Sign up to set email alerts
|

T Cells and Macrophages Responding to Oxidative Damage Cooperate in Pathogenesis of a Mouse Model of Age-Related Macular Degeneration

Abstract: Age-related macular degeneration (AMD) is a major disease affecting central vision, but the pathogenic mechanisms are not fully understood. Using a mouse model, we examined the relationship of two factors implicated in AMD development: oxidative stress and the immune system. Carboxyethylpyrrole (CEP) is a lipid peroxidation product associated with AMD in humans and AMD-like pathology in mice. Previously, we demonstrated that CEP immunization leads to retinal infiltration of pro-inflammatory M1 macrophages befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 59 publications
(81 reference statements)
4
66
0
Order By: Relevance
“…Many studies in animal models have established causal links between retinal damage and proinflammatory pathways [20][21][22]. In humans, many studies have shown that AMD patients presented higher expression of proinflammatory cytokines and altered phenotype and functions of immune cells [16,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies in animal models have established causal links between retinal damage and proinflammatory pathways [20][21][22]. In humans, many studies have shown that AMD patients presented higher expression of proinflammatory cytokines and altered phenotype and functions of immune cells [16,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…16 Moreover, Th1 cells and the proinflammatory macrophage subset M1 were two of the relevant cell types found in CEP-induced GA animal model. 17 However, the mechanisms of T-cell immunity in the onset of AMD pathology remains unclear.…”
mentioning
confidence: 99%
“…CFH can combine with C3b, inhibiting the formation of alternative-pathway C3 convertase, regulating and controlling the extent of complement activation (Yücel et al, 2012). Environmental factors such as obesity and smoking can interact with the CFH gene polymorphism, leading to reduced CFH expression and activation of the complement system, and therefore significantly increasing the concentrations of C5b-9 (membrane attack complex) and C3b (Atmaca et al, 2011;Schmitz-Valckenberg et al, 2011;Cruz-Guilloty et al, 2014). C5b-9 is deposited on the basement membrane of retinal pigment epithelium (RPE) cells, accelerating the formation of drusen.…”
Section: Discussionmentioning
confidence: 99%